2008
DOI: 10.1016/j.gie.2008.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Biochromoendoscopy: molecular imaging with capsule endoscopy for detection of adenomas of the GI tract

Abstract: We demonstrate proof of the principle that biochromoendoscopy-CE combined with molecular probes--provides a novel approach that differentiates adenomas from benign polyps and inflammatory lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 20 publications
(28 reference statements)
0
20
0
Order By: Relevance
“…Therefore, we are unable to attribute the observed fluorescent signals to specific tissues associated with PTOA development. However, each of these fluorescent activatable probes has been extensively validated and compared to histological standards [1219], and in particular have been validated for studies of musculoskeletal tissues [2023], therefore we are confident that the fluorescent signals are indicative of cellular processes at the level of the whole joint. Our future studies will utilize histological techniques to further characterize the specific tissues in which these fluorescent signals originate following traumatic joint injury using this animal model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we are unable to attribute the observed fluorescent signals to specific tissues associated with PTOA development. However, each of these fluorescent activatable probes has been extensively validated and compared to histological standards [1219], and in particular have been validated for studies of musculoskeletal tissues [2023], therefore we are confident that the fluorescent signals are indicative of cellular processes at the level of the whole joint. Our future studies will utilize histological techniques to further characterize the specific tissues in which these fluorescent signals originate following traumatic joint injury using this animal model.…”
Section: Discussionmentioning
confidence: 99%
“…These optical tracers are fluorescently quenched until a linker domain is cleaved by a specific protease of interest, which then produces a robust fluorescent signal. These techniques have been extensively validated and used in studies of cancer [1215] and atherosclerosis [1619], but are also potentially useful for studies of the musculoskeletal system to measure markers of inflammation and matrix degradation (cathepsin proteases and matrix metalloproteinases (MMPs)) and bone turnover (cathepsin K), which have vital roles in OA progression. Commercially available fluorescent activatable probes have been validated for use in musculoskeletal applications [2023].…”
Section: Introductionmentioning
confidence: 99%
“…During colonoscopy after orthotopic tumor induction, white light and NIR images could be displayed simultaneously, and pseudocolored overlay images were constructed at real time to assist in the detection of small lesions. Such imaging has also been performed with capsule endoscopy(12). In a proof-of-principle approach, a commercially available capsule has been equipped with a filter device capable of NIR imaging in addition to white light imaging.…”
Section: Preclinical and Clinical Studies Using Molecular Imaging In mentioning
confidence: 99%
“…The high target-to-background ratios generated by fluorescence probes, as well as the tissue penetration of fluorescent NIR photons, may augment our ability to visualize adenomas through thin mucosal folds. Also, flat lesions, which more commonly develop in patients with inflammatory bowel disease, are well identified via protease-activatable probes and can be differentiated from the inflammatory milieu in which they tend to arise (133).…”
Section: Improved Detection Of Colorectal Cancermentioning
confidence: 99%
“…A recent randomized controlled trial showed that conventional capsule endoscopy is inferior to colonoscopy for colorectal cancer screening (118). However, Zhang et al (133) have performed a proof-of-principle experiment using optical molecular imaging to potentially increase the sensitivity and specificity of capsule endoscopy for adenoma detection (1). After injecting APC Min/ϩ mice with a protease-activatable probe, they harvested the colon and fixed it onto a stage that steadily translated the colon under an optical setup that comprised of a clinical capsule endoscope and NIR filters.…”
Section: Potential For Clinical Translationmentioning
confidence: 99%